2015
DOI: 10.1002/psc.2843
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering and functional characterization of arenicin shortened analogs with enhanced antibacterial activity and cell selectivity

Abstract: New bioengineering approaches are required for development of more active and less toxic antimicrobial peptides. In this study we used β-hairpin antimicrobial peptide arenicin-1 as a template for design of more potent antimicrobials. In particular, six shortened 17-residue analogs were obtained by recombinant expression in Escherichia coli. Besides, we have introduced the second disulfide bridge by analogy with the structure of tachyplesins. As a result, a number of analogs with enhanced activity and cell sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 38 publications
2
38
0
1
Order By: Relevance
“…The cytotoxic effects were evaluated 48 h after peptide addition by MTT testing [8]. The results were processed statistically using GraphPad PRISM 6.0 software.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cytotoxic effects were evaluated 48 h after peptide addition by MTT testing [8]. The results were processed statistically using GraphPad PRISM 6.0 software.…”
Section: Methodsmentioning
confidence: 99%
“…For evaluation of the non-specific effect of tachyplesin I on human erythrocytes, hemolytic test was performed [8]. The data obtained in triplicates in two independent experiments are presented as the M±SD.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Ar-1[V8R] caused 50% cell death at concentrations of >100 µM in the presence of FBS and of 52 µM in the absence of FBS. It was reported that the decreased peptide cytotoxicity in the presence of FBS could be caused by antimicrobial peptides binding to serum components [10]. Notably, Ar-1[V8R] was not bound to erythrocytes at 25 µM (Fig.S5), while the wildtype arenicin-1 caused significant hemolysis at the same concentration.…”
Section: Cytotoxic Properties Of Arenicin-1 and The Ar-1[v8r] Analogmentioning
confidence: 90%
“…In particular, the suspension of hRBS with peptide was incubated in U-bottom polypropylene microplate (Corning) for 24 h at 37°C under stirring at 900 rpm. The colorimetric 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) dye reduction assay was used to determine cytotoxicity of the peptides on human embryonic fibroblasts (HEF) as described previously [10]. The experiment was performed in DMEM/F12 medium both with and without 10% fetal bovine serum (FBS, Gibco) for 24 h. The quantitative data were presented as an average means of the values measured in triplicate experiments with standard deviations.…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation